Induction of Biofilm Formation in Klebsiella pneumoniae ATCC 13884 by Several Drugs: The Possible Role of Quorum Sensing Modulation (2018)
ABSTRACT: Bacterial resistance is caused by several biochemical factors, the formation of biofilm being one of the main causes. This process is triggered by Quorum Sensing (QS), through the production of endogenous molecules, although other substances such as natural products can also do this. In this work, we aimed to determine whether some drugs are involved in the induction of biofilm formation in Klebsiella pneumoniae ATCC 13884, and thus, increase bacterial resistance. For this, the effect of 22 drugs on K. pneumoniae ATCC 13884 growth was determined at sub-plasmatic concentrations; the production of autoinducer lactones was established by HPLC and with a biosensor. The induction of biofilm formation was determined through crystal violet assay at 585 nm in a microplate reader and using urethral catheters. According to the in vitro assays, some drugs were found to induce biofilm formation in K. pneumoniae ATCC 13884. The effect of acetaminophen, hydrochlorothiazide, and progesterone stood out. The first drug caused several changes in the biochemistry of K. pneumoniae ATCC 13884 related to QS: high synthesis of N-hexanoyl-homoserine lactone, increasing bacterial populations by 27% and biofilm formation by 49%, and a more gentamicin resistant biofilm. Furthermore, it increased the colonization area of urethral catheters. Hydrochlorothiazide showed the biggest increase in the induction of biofilm formation of 51%, and progesterone displayed the greatest ability to provoke bacterial mass adherence but had no effects on K. pneumoniae ATCC 13884 bacterial population growth.